PERAN TASAWUF DALAM PEMBENTUKAN KARAKTER RELIGIUS MUSLIMAT NU YANG TANGGUH BAGI MASYARAKAT DUSUN KASENGAN DESA SUMBERKATIMOHO - Hasana, Nur; Rusly, H. Fathullah; Islam, Saiful (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to examine the role of Sufism in shaping the strong religious character of the Muslimat Nahdlatul Ulama (NU) in Kasengan Hamlet, Sumberkatimoho Village. A resilient religious character is essential amid social dynamics and the challenges of modern times. This research uses a descriptive qualitative approach with observation, interviews, and documentation methods. The findings show that Sufi practices such as dzikir, tahlil, shalawat, and khotmil Qur’an, regularly carried out by the Muslimat NU, contribute significantly to forming patient, humble, disciplined, and compassionate characters. Sufism serves not only as spiritual teaching but also as a powerful tool for moral and social development. Through religious activities rooted in Sufi values, the Muslimat NU in Kasengan Hamlet have become role models within their community. This study highlights that Sufism plays a crucial role in forming a religious personality that is not only spiritually devoted but also resilient in facing various social life challenges.